Beyond jump height: a comparison of concentric variables in the squat jump, countermovement jump and drop jump for athletic profiling - Kyne, H.; Cronin, J. B. (Sports, 2025)
Jump height provides limited insight into movement strategies and muscle-tendon unit (MTU) contraction dynamics of the squat jump (SJ), countermovement jump (CMJ), and drop jump (DJ). This study investigated whether concentric phase variables differ significantly across these jumps. Twenty-three male athletes (age: 18.1 ± 0.7 years) from various sports performed the SJ, CMJ and DJ on a force plate. Variables included jump height (JH), concentric duration (ConT), concentric mean force (CMF), relative concentric mean force (rCMF), and concentric force index (CFI). Significant differences (p < 0.05) were observed in all variables across jump types. The CMJ led to the greatest JH (37.8 ± 4.1 cm) compared to SJ (34.6 ± 4.4 cm) and DJ (31.9 ± 5.0 cm). Conversely, the DJ produced the greatest rCMF (30.1 ± 2.7 N/kg) within the shortest ConT (125 ± 15 ms), compared to the SJ (16.2 ± 0.8 N/kg in 409 ± 48 ms) and CMJ (19.8 ± 1.0 N/kg in 273 ± 24 ms). Minimal shared variance and varied individual athlete rankings across jumps suggest that each jump elucidates different facets of MTU function. As a novel variable, the CFI showed poor correlation with JH (r = -0.103 to 0.002), suggesting it may provide insights beyond jump height alone. These findings support our hypothesis that SJ, CMJ, and DJ offer distinct diagnostic insights into varying MTU contraction dynamics and the physical components underpinning jump performance, indicating that longitudinal monitoring of the CFI and underlying components (rCMF/ConT) across these jumps could enhance athletic profiling.